Konversi Agama Perempuan Etnis Cina Blangpidie Ke Islam (Kajian Sejarah dan Dinamika Islam di Abdya) (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2024)
The existence of ethnic Chinese in Blangpidie before Indonesia's independence and even until now has carried out religious conversion. This study aims to determine what factors influence the decision of Chinese women to convert to Islam in Blangpidie and the form of social interaction between converts and the community in Blangpidie in everyday life. This study uses a qualitative approach to make it easier to obtain valid data through interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, and verification/conclusions. The results of the study indicate that there are several factors that influence the decision of Chinese women to convert, namely divine factors, psychological factors, educational factors, mental/mental pressure factors, and social factors. The form of social interaction between converts and the community in Blangpidie in everyday life is very good in behavior, mutual respect, respect for others, mutual help between each other, love of peace and harmony. This can be seen from the form of cooperation and concern that exists between converts and the Blangpidie community.
Keywords: religious conversion; women; chinese ethnicity